Effects of induced electric field and high-pressure microjet sterilization on the physicochemical properties of milk - Huiyu Xiang; Weibing Tao; Yilong Li; Weiwei Mu; Yiting Cheng; Wei Shen; Chenhao Wang; Lijun Guan; Kunlun Wang; Xiaomeng Sun; Chun Li (Food Science of Animal Products)
This study aimed to investigate the difference between low-temperature sterilization methods including induced electric field (IEF) technology and the high-pressure microjet (HPM) and traditional thermal treatment including pasteurization and ultra-high temperature (UHT) sterilization on the sterilization effect and physicochemical properties of milk. The number of harmful colonies, particle size, thermal properties, protein secondary structure, and microstructure were characterized. Results demonstrated that low-temperature sterilization methods were equally effective as thermal sterilization methods. Differential scanning calorimetry results indicated that UHT treatment had enhanced the thermal stability of proteins in milk, while IEF treatment had improved the thermal stability of fats in milk. IEF sterilizing milk (IM) sample exhibited the largest particle size, followed by UHT sterilization milk (UM), raw milk (RM), and pasteurization milk (PM) according to the results of microstructure and size distribution. HPM sterilizing milk (HM) had the smallest particle size due to high pressure. Fourier transformed infrared spectra revealed that UHT sterilization changed the structure of milk protein due to the interactions between proteins, and protein-lactose. Conversely, the low-temperature sterilization methods had less effect on the protein structure. In conclusion, IEF and HPM have the similar sterilization effects to that of thermal sterilization methods, but have less effects on heat sensitive proteins, which has reference significance for the updating of sterilization technology in food field.